Carbon Storage in Cold Temperate Ecosystems in Southern Patagonia, Argentina. - Peri, Pablo Luis (inTech, 2011)
Recently there has been an increasing interest of research related to improve the understanding of carbon (C) sequestration mainly under Article 3.4 of the Kyoto Protocol of the United Nations Framework Convention on Climate Change where countries can count this sequestration as a contribution to reduce greenhouse gas emission (IPCC, 2001). Data on C storage in forests, grasslands and shrublands are essential for understanding the importance of rapidly increasing level of CO2 in the atmosphere and its potential effect on global climate change. In South America, mean annual temperature is predicted to increase by 3-4 °C in both summer and winter between 30° and 55° SL (Manabe & Wetherald, 1987). Such an increase would have significant effects on Patagonian ecosystems. In this context, secondary indigenous forests are considered efficient C sink ecosystems. Nothofagus antarctica (ñire), one of the main deciduous native species in the Patagonian region (Argentina), covers 751.643 hectares over a wide latitudinal (from 36° 25' to 54° 53' SL) and altitudinal (near sea level to 2000 m.a.s.l.) distribution. These forests occur naturally in different habitats such as poorly drained sites at low elevations, exposed windy areas with shallow soils, depressions under cold air influence, or in drier eastern sites near the Patagonian steppe (Veblen et al., 1996). These forests provide a range of wood products including poles, firewood and timber for rural construction purposes. Site quality for N. antarctica ranges from tall trees up to 15 m in dominant height on the best sites to shrubby trees of 2 m tall on rocky, xeric and exposed sites, and also in poorly drained sites. Previous research has highlighted the importance of stand age on the magnitude of C pools in both forest biomass and forest floor pools (Silvester & Orchard, 1999; Davis et al., 2003). Largescale canopy disturbance in N. antarctica forests may occur as a result of blowdown, snow avalanches or fire. This results in abundant regeneration (100,000 ...